2020
DOI: 10.1038/s41396-020-0717-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular symbionts drive sex ratio in the whitefly by facilitating fertilization and provisioning of B vitamins

Abstract: Symbionts can regulate animal reproduction in multiple ways, but the underlying physiological and biochemical mechanisms remain largely unknown. The presence of multiple lineages of maternally inherited, intracellular symbionts (the primary and secondary symbionts) in terrestrial arthropods is widespread in nature. However, the biological, metabolic, and evolutionary role of co-resident secondary symbionts for hosts is poorly understood. The bacterial symbionts Hamiltonella and Arsenophonus have very high prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 66 publications
2
73
0
Order By: Relevance
“…With regard to the S-symbionts, both Hamiltonella and Rickettsia genomes keep most of genes involved in synthesis of two EAAs: phenylalanine (Phe) and lysine (Lys), which are missing in the genome of Portiera [ 4 , 17 , 18 , 19 , 20 , 21 ]. In the present study, lower quantities of Hamiltonella and higher quantities of Rickettsia were found in the whitefly populations on eggplants, a more-nitrogen diet ( Figure 2 and Figure 5 ); the former showed similar changes with Portiera amounts in response to different host plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the S-symbionts, both Hamiltonella and Rickettsia genomes keep most of genes involved in synthesis of two EAAs: phenylalanine (Phe) and lysine (Lys), which are missing in the genome of Portiera [ 4 , 17 , 18 , 19 , 20 , 21 ]. In the present study, lower quantities of Hamiltonella and higher quantities of Rickettsia were found in the whitefly populations on eggplants, a more-nitrogen diet ( Figure 2 and Figure 5 ); the former showed similar changes with Portiera amounts in response to different host plants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicated that Hamiltonella can synthesize biotin; biotin provisioned by whitefly horizontally transferred genes (HTGs) affects the survival and fecundity of adult whiteflies [ 22 ]. A Hamiltonella deficiency reduced the level of B vitamin but not EAAs and affected the sex ratio, so this symbiont affects sex ratios in B. tabaci MEAM1 by regulating the fertilization and supplying B vitamins [ 21 ]. Except for the nutritional functions, S-symbionts may confer ecologically important traits, e.g., a resistance to parasitoids, thermotolerance, viral transmission, and hosts’ susceptibility to insecticides [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After more than two decades of research, experimental work directly measuring the costs and benefits of hosting symbionts in aphids is being replaced by work aiming to understand the ecological and evolutionary consequences of these interactions, and the mechanisms behind specific effects (Oliver & Higashi, 2019; Tian et al, 2019). For whitefly, most of the work is on a single species and its symbionts, with more recent focus on understanding mechanisms underlying these interactions (Santos‐Garcia et al, 2020; Wang, Ren, et al, 2020; Zchori‐Fein et al, 2014). For other plant‐sucking insects, work to identify a symbiotic microbiome is just starting, particularly for many Heteropterans that rely on diverse gut bacteria for digestion, nutrient synthesis or toxin degradation (Moran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The secondary symbionts have diverse effects on their hosts. For example, the Rickettsia confers general benefits to host fitness ( Himler et al, 2011 ) and assists its host in resistance to entomopathogen Pseudomonas syringae in MEAM1 whitefly ( Hendry et al, 2014 ); the Hamiltonella influences host sex ratio via provisioning of nutrients in MEAM1 whitefly ( Shan et al, 2019 ; Wang Y. B. et al, 2020 ), and some Cardnium and Rickettsia strains confer lower host fitness in B. tabaci MED and SSA1-SG3 species, respectively ( Fang et al, 2014 ; Ghosh et al, 2018 ; Zhao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%